The relationship between learning strategies and motivation to learn among students of the Third College of Education at Al-Baath University - Mosse, Ahmed Haj (Al-Adab Journal, 2015)
This research aim to recognize relationship between learning strategies and Motivation at third college education students, and known differences of means on learning strategies and Motivation scales according to three type variable: sex, specific, and study years. To achieve this aims, the researcher used Pintrich’s scale (1991) for measuring the learning strategies, Pintrich’s scale (1991) for measuring the Motivation toward learning. The research sample consist of (260) student male and female in Albaath University. This study get to the following results: There were significant statistical Correlation at the 0.05 level of significance, Between the (learning strategies and Motivation) There were no significant statistical differences at the 0.05 level of significance among the study groups on Motivation scale according to study years variable. There were no significant statistical differences at the 0.05 level of significance among the study groups on learning strategies and Motivation scales according to sex, and specific variables. There were significant statistical differences at the 0.05 level of significance among the the study groups, according to study years variable, In favour of the year one students.